Diseño de un molde de inyección de plástico-polipropileno para la fabricación de un comedero para perros (2017)
In order to carry out the development of the mold, a detailed examination of the current situation in the injection process was carried out to start from a base and then continue with the development of the project in which customer requirements based on A prototype of a presented channel. Subsequently, the possible design alternatives in the mold cooling system were discussed, followed by the evaluation and selection of one of these alternatives. Calculations were made of the mechanical parts that are present in the mold based on the loads and pressures to which it would be subjected. The design was made using specialized software such as Solid Edge in which plans were developed and explored the entire mold, It was then subjected to a finite element analysis using the NX 9.0 program in which data were obtained, such as the temperature and the stresses to which it would be submitted, which served to corroborate and support the calculations. Finally the manuals were made for the assembly and disassembly of the mold and maintenance of this one, also a financial evaluation was made to know the viability of the project.